Gamifying Flipped Classes: An Experience Report in Software Engineering Remote Teaching - Olivindo, Mayara; Veras, Necio; Viana, Windson; Cortés, Mariela; Rocha, Lincoln (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2021: Anais do XXXV Simpósio Brasileiro de Engenharia de Software, 2021)
Context. In the COVID-19 pandemic, higher education was one of the most affected in adapting the teaching-learning process to comply with social distance measures. In this context, this research reports how we combined two active methodologies in Software Engineering Emergency Remote Teaching. Objective. Therefore, this study aims to report the experiences obtained from the application of gamified study guides in Software Engineering (SE) between November 2020 and April 2021. Method. We combined flipped classroom, an active methodology already known by them, with Gamification to improve students’ acceptance and engagement. We created six gamified study guides for the SE flipped classes. 51 students participated in the classes, 12 students from the Computer Technician course and 39 students from the Computer Science Bachelor course. Each study guide had a group of checkpoints to organize the content in levels. Results. At the end of the application, we observed 83.6% of the participating students maintained their engagement. According to self-declaration, 85% felt motivated by the approach adopted, with 75.9% considering that the class format presented enhanced their learning. We also observed a positive impact on learning gain in an average of 18.3% in their grades. Final Considerations. We concluded that using Gamification and Flipped Classroom has positive impacts on learning and acceptance, although the COVID-19 pandemic and the ERT negatively affect students’ motivation.